2019
DOI: 10.1016/j.tranon.2018.09.001
|View full text |Cite
|
Sign up to set email alerts
|

The Evolutionarily Conserved Cassette Exon 7b Drives ERG's Oncogenic Properties

Abstract: The oncogene ERG encodes an ETS family transcription factor and is implicated in blood, vascular, and bone development and in prostate, blood, and bone cancer. The ERG gene is alternatively spliced; of particular interest is its cassette exon 7b which adds 24 amino acids, in frame, to the transcriptional activation domain. Higher exon 7b inclusion rates are associated with increased cell proliferation and advanced prostate cancer. The 24 amino acids encoded by exon 7b show evolutionary conservation from humans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 31 publications
2
9
0
Order By: Relevance
“…Mutation of the ERK docking site to AAAP prevents phosphorylation of ERG by ERK 15 . In our hands, and consistent with these findings, the reduction of exon 7b inclusion induced with splice-switching oligonucleotides (SSOs) resulted in decreased cell proliferation, migration and increased apoptosis 14 confirming that exon 7b contributes to ERG's oncogenic potential. These findings are consistent with earlier observations by Wang and colleagues who demonstrated that ERG isoforms that include 7b are more efficient in driving cell proliferation 16 .…”
Section: Introductionsupporting
confidence: 84%
See 2 more Smart Citations
“…Mutation of the ERK docking site to AAAP prevents phosphorylation of ERG by ERK 15 . In our hands, and consistent with these findings, the reduction of exon 7b inclusion induced with splice-switching oligonucleotides (SSOs) resulted in decreased cell proliferation, migration and increased apoptosis 14 confirming that exon 7b contributes to ERG's oncogenic potential. These findings are consistent with earlier observations by Wang and colleagues who demonstrated that ERG isoforms that include 7b are more efficient in driving cell proliferation 16 .…”
Section: Introductionsupporting
confidence: 84%
“…SSOs can promote the inclusion of desirable exons (e.g. TOES, targeted oligonucleotide enhancers of splicing 29 ), or induce exon skipping as illustrated by our own ERG exon 7b SSO 14 and Eteplirsen 27 . Another success story is Nusinersen, an FDA-approved ASO (Spinraza, Biogen) that is used to treat spinal muscular atrophy (SMA).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shon et al [39] indicated that ERG is highly expressed in osteosarcoma tissues, and suggested ERG as a possible marker of chondroid/ cartilaginous differentiation. In the study conducted by Jumbe et al [40], ERG was demonstrated to increase the bone matrix formation and promote osteosarcoma development via activating the transcription of TNSALP . Consistent with their studies, we also observed the upregulation of ERG in osteosarcoma cells and the pro-proliferating and pro-metastatic effect of ERG.…”
Section: Discussionmentioning
confidence: 99%
“…ERG is a widely investigated oncogene, involving in hematopoiesis, chondrocyte maturation, and bone development and in apoptosis and cell migration. [18] Due to the gene fusion with the promoter region of the androgen-induced TMPRRSS2 gene, ERG has become highly correlated with prostate cancer development. [19] RRM2, as the small subunit of ribonucleotide reductase, is an essential enzyme involved in DNA replication and repair.…”
Section: Discussionmentioning
confidence: 99%